Growth vs Value: A GARCH-APT Approach to Analyzing IDX Market Indices - Sihombing, Pardomuan; Triadji, Iwan (Research of Finance and Banking, 2025)
Value and growth investing strategies are often compared in the investment world. This study analyzes the differences in performance of the IDX Value30 and IDX Growth30 indices as a representation of these strategies in Indonesia during the period from January 30, 2014, to September 30, 2022. Measurements were made using the Treynor Ratio, Information Ratio, and stock selection and market timing evaluations through the GARCH (1,1) model. In addition, the APT model was also used to test the influence of macroeconomic factors, such as inflation, IDR/USD exchange rate, and 5-year Government Bond Yield. The comparison of Treynor and Information Ratio was tested using the Mann-Whitney and independent sample t-test. The results show that both indices have positive performance ratios but are not significantly different. Both do not show stock selection capabilities, but IDX Value30 has market timing capabilities. The IDR/USD exchange rate has a negative effect, and the 5-year Government Bond Yield has a positive effect on IDX Value30, while there are no significant macroeconomic factors on IDX Growth30. This research provides a new contribution through a comprehensive analysis of IDX Value30 and IDX Growth30, which can be used as a reference for investment strategies in the Indonesian capital market.